2008
DOI: 10.1007/s12160-008-9039-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Fruit and Vegetable Intake through Messages Tailored to Individual Differences in Regulatory Focus

Abstract: Background-Researchers must identify strategies to optimize the persuasiveness of messages used in public education campaigns encouraging fruit and vegetable (FV) intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 15 publications
(31 reference statements)
4
42
0
3
Order By: Relevance
“…For example, Latimer et al (2007) demonstrate that information about a virtue act-a physical activity-framed in terms of prevention elicited positive feelings toward this act among people with a prevention-goal orientation, whereas the same activity framed in terms of promotion elicited positive feelings among people with a promotion-goal orientation. Similar results were found for messages encouraging other virtue acts such as the intake of fruit and vegetables (Latimer et al, 2008). In general, studies in the regulatory focus domain show that marketing messages that use a benefitcongruency approach enhance individuals' positive cognitive and emotional reactions; when there was a fit between consumer regulatory goals and the message appeal, overall persuasion increased (Chang & Chou, 2008), and the value consumers inferred from their choices or actions increased (Avnet & Higgins, 2006) as did their positive feelings and confidence about the choices made (Cesario & Higgins, 2008).…”
Section: Theoretical Backgroundsupporting
confidence: 80%
See 1 more Smart Citation
“…For example, Latimer et al (2007) demonstrate that information about a virtue act-a physical activity-framed in terms of prevention elicited positive feelings toward this act among people with a prevention-goal orientation, whereas the same activity framed in terms of promotion elicited positive feelings among people with a promotion-goal orientation. Similar results were found for messages encouraging other virtue acts such as the intake of fruit and vegetables (Latimer et al, 2008). In general, studies in the regulatory focus domain show that marketing messages that use a benefitcongruency approach enhance individuals' positive cognitive and emotional reactions; when there was a fit between consumer regulatory goals and the message appeal, overall persuasion increased (Chang & Chou, 2008), and the value consumers inferred from their choices or actions increased (Avnet & Higgins, 2006) as did their positive feelings and confidence about the choices made (Cesario & Higgins, 2008).…”
Section: Theoretical Backgroundsupporting
confidence: 80%
“…A growing body of research is focusing on benefit-congruency effects related to consumer regulatory goals. These studies explore congruency effects when a message's appeal matched the consumer's regulatory state (e.g., Cesario, Grant, & Higgins, 2004;Chang & Chou, 2008;Chernev, 2004) or regulatory disposition (e.g., Cesario & Higgins, 2008;Latimer et al, 2007;Latimer et al, 2008;Zhao & Pechmann, 2007). For example, Latimer et al (2007) demonstrate that information about a virtue act-a physical activity-framed in terms of prevention elicited positive feelings toward this act among people with a prevention-goal orientation, whereas the same activity framed in terms of promotion elicited positive feelings among people with a promotion-goal orientation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Other studies, both in and outside the lab, have shown how these strategic preferences can be taken advantage of to increase the effectiveness of self-regulation. For instance, several studies have demonstrated that when health messages take advantage of the principles of regulatory fit, individuals will be more persuaded to increase their consumption of fruits and vegetables (Cesario, Grant, & Higgins, 2004;Latimer, Williams-Piehota, et al, 2008;Spiegel, Grant-Pillow, & Higgins, 2004), increase physical activity (Latimer, Rivers, et al, 2008), and reduce intentions to smoke (Kim, 2006;Zhao & Pechmann, 2007).…”
Section: Self-control Conflictsmentioning
confidence: 99%
“…Messages that "fit"-either because the message fits the receivers' chronic orientation (e.g., Latimer, Williams-Piehota, et al, 2008) or because a message primes both a regulatory system (e.g., promotion) and the related strategy (e.g., eagerness) (Spiegel et al, 2004)-appear to increase the effectiveness of self-regulation through several channels. When individuals receive a message under conditions of regulatory fit, they have been shown to "feel right" about their experience of the message (Cesario et al, 2004;Cesario & Higgins, 2008), to experience greater processing fluency (Lee & Aaker, 2004), to have more positive feelings towards the focal activity (Latimer, Rivers, et al, 2008), to show greater accessibility for the message (Lee & Aaker, 2004), and to feel that it is more diagnostic (e.g., useful) for making behavioral choices (Zhao & Pechmann, 2007).…”
Section: Self-control Conflictsmentioning
confidence: 99%
“…The messages were designed to enhance and reinforce the idea that a healthy lifestyle (e.g., eating more fruits and vegetables and exercising) promotes health in many ways. Messages were designed using a well-established message development paradigm that has been tested in previous research [41,42]. …”
Section: Materials Designmentioning
confidence: 99%